The ‘language’ and ‘feel’ of bilingual memory: Mnemonic traces - Schrauf, Robert W; Rubin, David C (Sociolinguistic Studies, 2004)
How are language and emotion integrated in the mnemonic trace underlying reconstructive retrieval? Does remembering in the first versus the second language affect the feel of memories? In a protocol analysis of the kinds of information activated during memory search, Schrauf (2003) found that, as participants followed a train of associations in response to cue words, they most often evoked visual images (66%) vs. verbal (17%), feeling (13%), or conceptual (29%) associations. Because imagery is known to be a key factor in the mental re-experiencing of past events, this paper examines the interrelation of imagery with emotion and language in bilingual autobiographical memory. Thirty Spanish-English speaking Puerto Rican immigrants to the mainland US rated memories in both languages for visual, emotional, auditory, and linguistic detail. Multidimensional scaling analyses showed that visual detail and emotional intensity clustered together, suggesting that these are linked contributors to the sense of re-experiencing past events. Comparison of bilinguals’ recalls in Spanish vs. English showed more intensity of imagery and emotion in second language (English) than first language (Spanish) memories. We suggest that English memories are more recent, more novel, and require more effort-after-meaning (Bartlett, 1932) than Spanish memories and are therefore recalled with more imagistic detail and emotional intensity than Spanish memories.